2001
DOI: 10.1161/01.atv.21.4.529
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Differentially Regulates Induction of Type II Nitric Oxide Synthase in Rat Vascular Smooth Muscle Cells Versus Macrophages

Abstract: Abstract-We studied effects of nitric oxide (NO) released by different NO donors on induction of inducible NO synthase (iNOS) in rat aortic smooth muscle cells (RASMC) and rat macrophage cell line NR8383. iNOS protein expression induced by a CM (interleukin-1␤ 250 U/mL, interferon-␥ 150 U/mL, and tumor necrosis factor-␣ 150 U/mL) was not affected by the NO donor SNAP (0.2 to 1 mmol/L) in RASMC at 24 hours of incubation but was dose-dependently decreased by SNAP in macrophages (maximal 60% inhibition). A fully … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
(32 reference statements)
2
4
0
1
Order By: Relevance
“…LPS- and LPS/IFN γ -induced generation of • NO by macrophages was not affected by the • NO donor NOC-18 (1–50 μ M), even at concentrations that far exceed any possible • NO concentration that might be derived from nitroalkene decay in assay systems (results not shown). Therefore CLNO 2 -mediated inhibition of macrophage activation could not be explained by an ability to release • NO, as described previously [17,31,32]. Of note, • NO-mediated attenuation of NOS2 expression frequently requires high, non-biological concentrations of • NO [32] that may be transduced by mechanisms shown in the present study.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…LPS- and LPS/IFN γ -induced generation of • NO by macrophages was not affected by the • NO donor NOC-18 (1–50 μ M), even at concentrations that far exceed any possible • NO concentration that might be derived from nitroalkene decay in assay systems (results not shown). Therefore CLNO 2 -mediated inhibition of macrophage activation could not be explained by an ability to release • NO, as described previously [17,31,32]. Of note, • NO-mediated attenuation of NOS2 expression frequently requires high, non-biological concentrations of • NO [32] that may be transduced by mechanisms shown in the present study.…”
Section: Resultssupporting
confidence: 76%
“…Therefore CLNO 2 -mediated inhibition of macrophage activation could not be explained by an ability to release • NO, as described previously [17,31,32]. Of note, • NO-mediated attenuation of NOS2 expression frequently requires high, non-biological concentrations of • NO [32] that may be transduced by mechanisms shown in the present study. Thus additional pathways appear to be involved in signalling actions linked to nitroalkene-mediated control of NOS2 expression.…”
Section: Resultssupporting
confidence: 76%
“…In vivo, it has been shown in burned rats that arginine supplementation leads to a decrease in TNFa production (Cui et al, 2000). Given that Sinha et al (1998) have demonstrated in RAW 264.7 cells that NO down-regulates TNF mRNA, it can be hypothesised that our observation is related to the biphasic regulation of NOS and NF-kB (Connelly et al, 2001;Zhang et al, 2001) discussed above. Since NF-kB is a major regulator of cytokine expression, the higher NO production in macrophages from obese rats at the higher arginine concentrations may induce an inhibition of NF-kB activity and thus a decrease in TNFa release.…”
Section: Discussionmentioning
confidence: 65%
“…However, regulation of iNOS expression is predominantly governed by the transcription factor NF-kB and a biphasic effect of NO on NF-kB has been shown (Connelly et al, 2001) that depends on local NO concentration, high NO concentration leading to an inhibition of NF-kB activity eliciting an inhibition of iNOS expression. It has been further proposed that this inhibitory effect of NO occurs via a decrease in NF-kB DNA-binding activity (Zhang et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Це індуцибельна форма NOS, не залежна від внутрішньоклітинної концентрації іонів кальцію, наслідком активації якої є гіперпродукція оксиду азоту аж до цитотоксичних рівнів. В індукці цього типу ферменту беруть участь прозапальні ци-токіни, ендотоксини [17]. Третій тип NOS -ендотелі-альний фермент (за місцем первинного виявлення), це конституціональний мембранозв'язаний фермент, що регулюється вмістом кальцію.…”
unclassified